DIRECTIVE SPEECH ACT IN THE HUNGER GAMES MOVIE - Salwa Muhamad; Priska Meilasari (Universitas Katolik Widya Mandala Surabaya, 2022)
TheÂ research is titled â€œDirectives Speech Act in The Hunger Games Movieâ€ The research aimed to find outÂ and classify the types of directive speech acts used in The Hunger Games Movie and explain the linguistic form of each type of directive speech act based on the contexts. The method applied was the descriptive qualitative method. The data of this research were in the form of words and sentences that contain directive speech acts. The technique of collecting data was conducted by collecting the data from The Hunger Games movie, classifying types of directive speech act, and describing the form of each type of directive speech act. Furthermore, the technique of data analysis was based on Kreidler's (1998) classification of directive speech acts. The types are commands, requests, and suggestions. The next step was explaining the form of each type of directive speech acts based on the pragmatic contexts. The findings of this study showed that request interrogative is the most dominant type of directive used with a total number 117 utterances or 32,47% in percentage.Keywords:Â Pragmatic, Speech Act, Directive speech act